Climate-Smart Agriculture: Technological Innovations for Food Security and Environmental Sustainability - Muhammad Hamza Qureshi; Iqra Riaz (Global Journal of Multidisciplinary and Applied Sciences, 2025)
Climate-smart agriculture (CSA) has emerged as an integrative approach to transform agri-food systems under escalating climate risks, aiming to (i) sustainably increase productivity and incomes, (ii) strengthen adaptation and resilience, and (iii) reduce or remove greenhouse gas (GHG) emissions where feasible. This article synthesizes key technological innovations that operationalize CSA—digital decision support, precision input management, stress-tolerant germplasm, climate-informed water solutions, soil carbon and nutrient technologies, and low-emission livestock interventions—showing how these innovations can jointly support food security and environmental sustainability. Evidence from global assessments highlights that land and agricultural interventions involve important co-benefits and trade-offs across mitigation, adaptation, biodiversity, and food security, requiring systems-level planning and careful governance. We propose a practical five-part framework for deploying CSA technologies, emphasizing data infrastructure, farmer-centered design, inclusive finance, and robust monitoring to accelerate adoption—particularly relevant for climate-vulnerable contexts such as Pakistan.